Regulación de la temperatura en Chaetophractus villosus - V. G., Roig; O. E., Henriquez (Ecosur, 2024)
Chaetophractus villosus body temperature was observed by means of teletermometers placed at different body depths while kept in captivity in chambers of constant temperature. At a periferical level high variations were recorded. Below 4-5 cm depth temperature variations were alternated until a termical gradient is reached. Nictimeral rithms are showed in nocturnal activity, being, ore evident in reponse to the environmental temperature. Coments about feeding behavior, ecology and fisiology are included. General considerations about filogeny of termo regulation are also given.